Answer:
B) 2
Explanation:
Alright. So you have 7x - 3 + 4x = 19.
Combine like terms, and you get 11x - 3 = 19.
If you know how to solve 2-step equations, this will be easy! I'll explain it either way though :)
1. You want to get rid of adding/subtracting first by canceling the number out. In this situation, that number is 3.
11x - 3 = 19
+ 3 + 3
11x = 22
2. Then you want to get rid of multiplying/dividing by doing the same. You want to get the variable all by itself.
11x = 22
11x/11 = 22/11
x = 2
Hope this helped! :)